An International Comparison of Women's Health Issues in the Philippines, Thailand, Malaysia, Canada, Hong Kong, and Singapore: The CIDA-SEAGEP Study - Bernard Choi (The Scientific World Journal)
This was an international study of women's health issues, based on an Official Study Tour in Southeast Asia (the Philippines, Thailand, Malaysia, Hong Kong, and Singapore) and Canada. The objectives of the study were to identify and compare current gaps in surveillance, research, and programs and policies, and to predict trends of women''s health issues in developing countries based on the experience of developed countries. Key informant interviews (senior government officials, university researchers, and local experts), self-administered questionnaires, courtesy calls, and literature searches were used to collect data. The participating countries identified women's health as an important issue, especially for reproductive health (developing countries) and senior's health (developed countries). Cancer, lack of physical activity, high blood pressure, diabetes, poverty, social support, caring role for family, and informing, educating, and empowering people about women's health issues were the main concerns. Based on this study, 17 recommendations were made on surveillance, research, and programs and policies. A number of forthcoming changes in women's health patterns in developing countries were also predicted.